Avaliação do efeito do ácido gálico no tratamento de células de hepatocarcinoma HEPG2 - Lima, Kelly Goulart (2014)
Hepatocellular Carcinoma is the most prevalent primary tiver tumor and is among the top ten cancers that affect the world population. lts development is related, in most cases, the existente of chronic tiver injury, such as occurs in cirrhosis. Current curative therapies are only surgical resection, transplantation and percutaneous ablation, however with the possibility of recurrence. In this context, the search for new therapies for the disease becomes an interesting field for research. The knowledge about the correlation between chronic inflammation and cancer has driven new researches with anti-inflammatory agents that have potential for the development of antitumor drugs. Gallic acid is a polyphenol found in many natural products and have shown anti-inflammatory activity, anti-tumor, antimutagenic and strong antioxidant action. The purpose of this study was to investigate the effect of gallic acid on cell proliferation and inflammatory parameters of tiver carcinoma cells (HepG2), as well as to investigated the mechanisms involved. Cell viability was evaluated through MTT colorimetric assay and Trypan blue exclusion. Results showed that the gallic acid decreased proliferation of HepG2 celis in a dose and time dependent manner, without causing necrosis (LDH assay). We observed significant induction of apoptosis by PE Annexin V and 7-AAD assay and no interferente with the cell cycle using the FITC BrdU Flow Kit. The leveis of inflammatory mediators were measured by Cytometric Bead Array Human Inflammation Assay and observed a significant reduction in the leveis of interleukin-8 (pro-inflammatory and related to angiogenesis, invasiveness and metastasis) and increased leveis of interleukin-10 (anti-inflammatory and related to the induction of programmed cell death) and interleukin-12 (antiangiogenic and antimetastatic). We also evaluated the leveis of TGF by ELISA (Enzyme-Linked lmmunosorbent Assay) and no significant differences. According to these results, we believe that gallic acid has a strong potential as an anti-tumor agent.